The effects of dietary supplement of galactooligosaccharide on innate immunity, immune related genes expression and growth performance in zebrafish (Danio rerio). Issue 73 (February 2018) - Yousefi, Samira; Hoseinifar, Seyed Hossein; Paknejad, Hamed; Hajimoradloo, Abdolmajid
Abstract: The present study investigates the effect of different levels of galactooligosaccharide (GOS) on innate immune parameters, immune related genes expression as well as growth performance in zebrafish ( Danio rerio ). Four hundred and twenty fish (mean weight 45 ± 0.1 mg) were supplied, randomly stocked in twelve aquaria assigned to four treatments. Zebrafish were fed with either control diet or control diet enriched with different levels (0.5, 1 and 2%) of GOS for eight weeks. At the end of feeding trial innate immune parameters (total immunoglobulin, total protein and alkaline phosphatase activity), immune related genes expression (interleukin 1 beta [ il1b ], Lysozyme [ lyz ], tumor necrosis factor alpha [ tnf-alpha ]) as well as growth performance were measured. Evaluation of immune parameters revealed significant ( P  < .05) increase of total protein and total Ig in zebrafish fed 1 or 2% GOS compared other treatments. However, in case of lysozyme activity no significant ( P  > .05) differences were noticed between GOS fed fish and control group. Also, in case of ALP activity, significant increase ( P  < .05) was observed in 2% GOS treatment. Gene expression studies revealed significant upregulation ( P  < .05) of tnf-alpha and lyz genes in GOS fed fish. While no significant ( P  > .05) difference was observed in case of il1b gene expression. Evaluation of growth performance at the end of feeding trial revealed no significant ( P  < .05) improvement in GOS fed groups. The present results revealed positive effects of GOS on innate immune parameters and related gene expression in zebrafish. Highlights: Galactooligosaccharide [GOS] improved innate immune parameters in Zebrafish. GOS upregulated the expression of immune related genes in Zebrafish. GOS had no remarkable effects on growth performance of Zebrafish.